Long-distance migration and homing after displacement in the green turtle (Chelonia mydas): A satellite tracking study - Luschi, P.; Papi, F.; Liew, H.C.; Chan, E.H.; Bonadonna, F. (Springer Verlag, 1996)
Four green turtle females were tracked by satellite during their post-reproductive migration in the South China Sea. Three of them reached their feeding grounds 923-1551 km distant. During nesting activity, a female was displaced twice, and her return trips to the nesting beach from 11 and 284 km were tracked by a direction-recording data-logger and by satellite, respectively. Part of the journeys occurred coastwise, indicating that leading geographical features had been utilised. The straightness of the turtles' tracks in open seas, both over shallow and deep waters, and their ability to pinpoint distant targets and home after displacement off their usual routes, provides circumstantial evidence for a true navigation mechanism.